2001
DOI: 10.1200/jco.2001.19.3.800
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Paclitaxel and Radiation in the Treatment of Locally Advanced Head and Neck Cancer

Abstract: Paclitaxel administered as a 120-hour continuous infusion in combination with radiotherapy is a feasible and promising treatment for patients with advanced HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 38 publications
3
29
0
1
Order By: Relevance
“…Complete tumor clearance was documented in 74% of the patients with an overall response rate of 71% and a 2 year survival of 32%. Sunwoo et al [25], administered Paclitaxel as a 120-hour continuous infusion every 3 weeks to 33 previously untreated patients with stage III or IV tumors. Sixteen patients received a Paclitaxel dose of 105 mg/m 2 , and 17 patients received 120 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Complete tumor clearance was documented in 74% of the patients with an overall response rate of 71% and a 2 year survival of 32%. Sunwoo et al [25], administered Paclitaxel as a 120-hour continuous infusion every 3 weeks to 33 previously untreated patients with stage III or IV tumors. Sixteen patients received a Paclitaxel dose of 105 mg/m 2 , and 17 patients received 120 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, bortezomib inhibited growth of murine and human SCC in mice, which was associated with a marked decrease in vessel density. In addition, bortezomib inhibited expression of proinflammatory and proangiogenic factors GRO-1 and VEGF by SCC in the range at which bortezomib inhibits NF-κB [71].…”
Section: Nf-κb Regulated Proteomes and Transcriptomes As Biomarkers Amentioning
confidence: 93%
“…The inhibitory activity of bortezomib has been demonstrated against a spectrum of cancer cells in culture [57][58][59][60][61][62][63][64][65][66][67] and in animal models [50,[68][69][70] including suppression of NF-κB and other signal transcription pathways with induction of cell apoptosis and cell cycle arrest. The molecular and clinical effects of bortezomib and potential mechanisms of sensitivity and resistance have been most extensively studied in multiple myeloma (MM) and certain other hematopoietic malignancies [58,[60][61][62][63], and to a lesser extent in solid cancers [31,50,57,[64][65][66][67][68]70,71].…”
Section: Nf-κb Regulated Proteomes and Transcriptomes As Biomarkers Amentioning
confidence: 99%
See 1 more Smart Citation
“…Paclitaxel (Taxol), a novel naturally occurring antineoplastic agent, has shown great promise in the treatment of a variety of tumor types including breast, head and neck, ovarian, and lung cancers (1)(2)(3). Although the exact mechanism of the cytotoxicity of paclitaxel against tumor cells is not entirely clear, previous studies demonstrated that paclitaxel is a unique antimicrotubule agent that acts by inhibiting microtubule depolymerization and thereby disrupting the normal dynamic reorganization of the microtubule network required for mitosis and cell proliferation (4,5).…”
Section: Introductionmentioning
confidence: 99%